Exploring the Role of Smoking in Platelet Count Changes Among Adult Men in Dhaka (Journal of Shaheed Suhrawardy Medical College, 2025)
Platelets are critical for haemostasis and thrombosis, serving as important indicator for physiological and pathological conditions. Smoking, a prevalent health risk globally, influences platelet function and may impact platelet count, yet the evidence remains inconsistent. This study explores the role of smoking in platelet count variations among adult men in Dhaka, assessing differences between smokers and non-smokers and examining the effects of smoking severity and duration. A case-control study was employed, involving 200 male participants (100 smokers and 100 non-smokers), aged 18–70 years. Participants were recruited from Bangabandhu Sheikh Mujib Medical University, Dhaka, from January to June 2022. Smoking history, demographic, and clinical data were collected via interviews and platelet counts were measured from blood samples. Statistical analyses, including t-tests, ANOVA, and Pearson’s correlation, were performed to evaluate differences and associations. A p-value < 0.05 was considered significant. The study found no significant difference in mean platelet counts between smokers (273.64 ± 100.48 cumm) and non-smokers (267.87 ± 79.86 cumm; p = 0.654). Analysis by smoking severity revealed the highest platelet counts among moderate smokers (285.2 ± 112.5 cumm), but differences were not statistically significant (p = 0.581). A weak negative correlation between smoking duration and platelet count was observed (r = -0.055, p = 0.586). While smoking severity and duration showed minimal impact on platelet counts, trends suggest potential interactions between smoking and hematological parameters. These findings align with studies reporting complex, dose-dependent effects of smoking on platelet activity. Differences in sample characteristics, environmental factors, and smoking habits may explain the absence of significant associations. This study highlights the need for further research on the interplay between smoking and platelet function. Findings provide localized insights that could inform public health strategies in Dhaka city while contributing to global understanding of smoking-related platelet count changes.J Shaheed Suhrawardy Med Coll 2023; 15(2): 40-44